TEACHING COVID-19 CONCEPTS TO LEARNERS: FILIPINO EARLY CHILDHOOD EDUCATORS’ NARRATIVES - Inero Ancho; Leonora Varela; Liza Legaspino; Abegail Karen Lee (Journal of Educational, Health and Community Psychology, 2023)
What are the challenges faced by early childhood educators in teaching COVID-19 concepts to Kindergarten learners? What strategies do these educators employ and how are these addressed? The present study is anchored on these initial inquiries seeking to gather the narratives of Filipino early childhood educators as they navigate the education landscape amid the health crisis. Phenomenological design is used in the study in exploring what Filipino ECEd teachers have experienced in teaching COVID-19 concepts to learners. Six Filipino ECEd teachers were the participants of the study, representing the three main islands of the Philippines — Luzon, Visayas, and Mindanao. They have been teaching for at least 3 years prior to the pandemic and are still currently in the profession where they have experienced teaching COVID-19 concepts to learners. The COVID-19 concept although may be challenging to introduce, still needs to be delivered to allow learners to gain an understanding of the pandemic situation. COVID-19 can be vague to some young learners, for that reason, it requires being familiar with new vocabulary and additional visual cues for better understanding. Also, the reality of deaths caused by the virus creates fear and worries not only for the learners but the teachers as well.  The many challenges brought by the COVID-19 compels ECEd teachers to modify and employ creative strategies to let their learners be equipped with skills to practice health and safety protocols.